Growing old paying for retirement and institutional money management after the financial crisis - Fuchita, Yasuyuki 1958-; Herring, Richard; Litan, Robert E. 1950- (Nomura Institute of Capital Markets Research, 2011)
"Explores issues in financing retirement, from fundamental changes in types of pension plans offered to pension funds' investment strategies following the global financial crisis. Focuses in particular on the adequacy of individuals' and institutions' plans in the face of increasing life expectancy and the aging of the population"--Provided by publisher.